Compound Heterozygous Missense Variants in RPL3L Genes Associated with Severe Forms of Dilated Cardiomyopathy: A Case Report and Literature Review - Bibhuti B. Das; Viswanath Gajula; Sandeep Arya; Mary B. Taylor (MDPI AG, 2022)
Whole exome sequencing has identified an infant girl with fulminant dilated cardiomyopathy (DCM), leading to severe acute heart failure associated with ribosomal protein large 3-like (RPL3L) gene pathologic variants. Other genetic tests for mitochondrial disorders by sequence analysis and deletion testing of the mitochondrial genome were negative. Secondary causes for DCM due to metabolic and infectious etiologies were ruled out. She required a Berlin-Excor left ventricular assist device due to worsening of her heart failure as a bridge to orthotopic heart transplantation. At three months follow-up after heart transplantation, she has been doing well. We reviewed the literature on published RPL3L-related DCM cases and their outcomes. Bi-allelic variants in RPL3L have been reported in only seven patients from four unrelated families in the literature. RPL3L is a newer and likely pathogenic gene associated with a severe form of early-onset dilated cardiomyopathy with poor prognosis necessitating heart transplantation.